Sosialisasi Pembuatan Pot Organik Dari Cocofiber Di SDN 2 Kampung Baru Bandar Lampung - Indri Maheswari; Tifani Rosma Dewi; Nazwa Shihab; Novia Nazila Ramadhani; Ester Virginia Samosir; Zulfa Emalia (Departement of Mathematics Education, 2024)
The socialization activity of making organic pots from cocofiber at SDN 2 Kampung Baru, Bandar Lampung, aims to increase the awareness of students and the community about environmentally friendly waste management. In this activity, students were invited to understand how to process cocofiber waste into useful organic pots. The methods used include counseling, demonstrations, and hands-on practice, so that students not only gain knowledge, but also practical skills in organic potting. This activity successfully increased students' creativity and gave them new insights on the importance of utilizing natural materials to reduce the negative impact of plastic waste. Through this activity, it is hoped that it can encourage efforts towards sustainable education that provides benefits for the environment and the surrounding community.